Historical Society, 1911 - Unknown (1911)
Members of the Historical Society at Missouri State Normal School of the First District in Kirksville, MO, in 1911. Front row, left to right: Eugene Fair, G.V. Baskett, W.H. Snyder, Helen Bradley, Carl Magee, C.M. Wise, Melvin E. Fish. Second row: Bruce I. Melvin, A.G. Reed, F.E. Patrick, Susan Case, Eva Dawson, Ina Baltzell, Frances Savage, Louise Koenemann, Mrs. J.A. Miller. Top row: John R. Murdock, H.D. Voss, E.D. White, E.M. Violette, Jessie Harding, Saloma Smith, Clara Habermeyer, A. Otterson.